Zines, Women, and Culture: Autobiography Through Self-Publication - Hodgson, Kate; Rae Biebrich, Tamara; Moore, Stefanie (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
Zines are texts that exist as overt and self-conscious sites of active resistance against culturally prescribed categories and identities. Homemade, xeroxed publications existing on the margins of canonical and commercial literature and art, zines offer a means of expression that in form and content challenge familiar representations of self in text. Zines provide documentation of women’s resistance, simultaneously questioning and reinscribing the borders of gender, identity, feminism and textuality. I engage zines as text through interviews with two Winnipeg women who are currently publishing zines, Stefanie Moore and Tamara Biebrich. Integrating female voices and women’s zine material, zines are shown as embodiments of women’s daily lives and work, a space for women to represent themselves outside of dominant cultural demands on publishing and form. Zines question the authority of mainstream texts, yet inhabit and move between counterculture and popular culture, crossing boundaries and complicating our notions of divisions between discourses.